Identification of Economic Impact Valuation on Small Industrial Centers (Study on the Sukaregang Leather Tannery Industrial Center) - Suryaman, Restu A (Universitas Gorontalo, 2024)
This research aims to identify the magnitude of the economic impact caused by the existence of small industrial centers by taking a case study of the Sukaregang leather tanning industrial center. The method used in this research is cost and benefit analysis to obtain a valuation value for the externalities that arise. This research was conducted qualitatively by collecting data through interviews, observation and expert judgment. The research results found that the positive economic impact resulting from the activities of the Sukaregang leather tanning industrial center was in the form of employment, growth of the leather craft industry, creation of a supporting tourism subsector and improvement in community welfare. Meanwhile, the negative economic impacts caused are environmental pollution, disruption of the quality of public health and disruption of clean water sources. The valuation of the positive economic impact generated is estimated at IDR 68,516,318,340 per year, while the valuation of the negative economic impact is estimated at IDR 65,701,500,000 per year. The research found that the positive economic impact is estimated to be greater than the negative economic impact with a gap that is not too large, so it is a recommendation for the government and business actors to pay attention to green economic aspects in the industrial sector so that economic activities and regional development can run sustainably.